The Effect of Accounting Information and Tax Information on Trading Value Moderated by Competitive Strategy - ., Suhendra; Murwaningsari, Etty (Journal of Accounting, Business and Finance Research, 2019)
This article is a research about the influence of accounting information and tax information on trading values with competitive strategies as a moderating variable in the Indonesia Stock Exchange. Accounting information was measured from the current ratio, tax information was measured from VAT, the trading value was measured by the logarithm of natural total trading value, and competitive strategy was measured by premium price capability (PPC). The sample in this research trading value stock company that was consistent in the last five years listed on the Stock Exchange during 2013-2017 as many as 15 companies. Data collection method used purposive sampling technique. Data analysis technique was multiple panel data regression analysis using Stata software. The results show that accounting information does not have a significant effect on value trading. Tax information has a significant negative effect on trading value. Competitive strategies have a significant positive effect on trading value. Competitive strategy is not able to significantly moderate the influence of accounting information on trading value. Meanwhile, competitive strategy can moderate positively and significantly negative impact on the effect of tax information on trading value.